1997
DOI: 10.1093/oxfordjournals.jbchem.a021838
|View full text |Cite
|
Sign up to set email alerts
|

Is the Cannabinoid CB1 Receptor a 2-Arachidonoylglycerol Receptor? Structural Requirements for Triggering a Ca2+ Transient in NG108-15 Cells

Abstract: The effects of delta9-tetrahydrocannabinol and 2-arachidonoylglycerol on the intracellular free Ca2+ concentration ([Ca2+]i) in NG108-15 cells were examined in detail. We found that delta9-tetrahydrocannabinol induces a rapid, modest increase in [Ca2+]i. The response was detectable with 3 nM delta9-tetrahydrocannabinol. We also found that very low concentrations of 2-arachidonoylglycerol elicit a rapid, more prominent increase in [Ca2+]i. Such a response was observed not only in NG108-15 cells but also in N18T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
78
3
2

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(86 citation statements)
references
References 0 publications
3
78
3
2
Order By: Relevance
“…In preceding studies, we investigated the mechanism and physiological meaning of 2-arachidonoylglycerol-induced transient increases in [Ca 2ϩ ] i in NG108 -15 cells (22,23). We established that the response induced by adding 2-arachidonoylglycerol to the cells is mediated through the cannabinoid CB1 receptor and G i or G o (22,23), yet the detailed mechanism is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In preceding studies, we investigated the mechanism and physiological meaning of 2-arachidonoylglycerol-induced transient increases in [Ca 2ϩ ] i in NG108 -15 cells (22,23). We established that the response induced by adding 2-arachidonoylglycerol to the cells is mediated through the cannabinoid CB1 receptor and G i or G o (22,23), yet the detailed mechanism is not yet fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…We established that the response induced by adding 2-arachidonoylglycerol to the cells is mediated through the cannabinoid CB1 receptor and G i or G o (22,23), yet the detailed mechanism is not yet fully understood. One important issue to be verified is whether or not 2-arachidonoylglycerol itself, but not its metabolites, is actually involved in this rapid cellular response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8) Previously, we investigated in detail the structure-activity relationship of cannabinoid receptor ligands and found that 2-AG is the most efficacious agonist among the various structural analogs and homologs thus far examined. [9][10][11] Importantly, 2-AG acted as a full agonist toward these cannabinoid receptors in various assay systems, [9][10][11][12][13][14] whereas anandamide often acted as a partial agonist. Based on these experimental results, we proposed that 2-AG, rather than anandamide, is the true natural ligand for the cannabinoid receptors.…”
mentioning
confidence: 99%
“…[9][10][11] 2-AG elicits a variety of biological responses in various nervous tissues and cells. 15) For example, 2-AG induced a Ca 2ϩ transient in NG108-15 cells, 9,10) the inhibition of longterm potentiation 16) and the inhibition of synaptic transmission 17) in rat hippocampal slices, and the inhibition of voltage-gated Ca 2ϩ channels and the activation of inwardly rectifying K ϩ channels in rat sympathetic neurons 18) via CB1 receptor-dependent mechanisms. On the other hand, not much information is available concerning the effects of 2-AG on inflammatory cells and immune-competent cells which express the CB2 receptor.…”
mentioning
confidence: 99%